THE ROLE OF SIMILES IN THE LANGUAGE SYSTEM AND LINGUISTIC ANALYSIS (World Bulletin of Social Sciences, 2025)
In this article, the role of similes in the language system and their study within the framework of linguistics is examined comprehensively and systematically. In particular, simile is considered as an important expressive tool at the lexical, semantic, and stylistic levels of language, and its functional significance in the speech process is highlighted.